2016
DOI: 10.1038/hr.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

A new modified blood pressure-to-height ratio simplifies the screening of hypertension in Han Chinese children

Abstract: The present study evaluated the simplicity and accuracy of a new modified blood pressure-to-height ratio (MBPHR3) in identifying hypertension among Han children aged 7-12 years. In 2011, anthropometric measurements were collected as part of a cross-sectional population-based study of 1352 Han children aged 7-12 years. Receiver operating characteristic curve analyses were performed to assess the accuracy of the modified systolic blood pressure-to-height ratio (MSBPHR3) and the modified diastolic blood pressure-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…6 The BPHT formulas were: SBP or DBP The present study described novel cut-off points for BPHT, MBPHT, and NMBPHT, which were built using new guideline data. 6 Consistent with studies based on the former guideline 10 for BP management in children, 4,5 we also showed that NMBPHT had greater performance to detect BP disorders. This superiority can be explained by the better ability of this formula to capture trunk's growth, 5 which is more correlated with BP than whole body's growth.…”
Section: New Modifications Of the Blood Pressure-to-height Ratio For supporting
confidence: 85%
See 1 more Smart Citation
“…6 The BPHT formulas were: SBP or DBP The present study described novel cut-off points for BPHT, MBPHT, and NMBPHT, which were built using new guideline data. 6 Consistent with studies based on the former guideline 10 for BP management in children, 4,5 we also showed that NMBPHT had greater performance to detect BP disorders. This superiority can be explained by the better ability of this formula to capture trunk's growth, 5 which is more correlated with BP than whole body's growth.…”
Section: New Modifications Of the Blood Pressure-to-height Ratio For supporting
confidence: 85%
“…The BP-to-height ratio (BPHT) is a simple screening tool that has shown good ability to identify high BP in children. 2 Conversely, variations in this formula, including the modified BP-to-height ratio (MBPHT) 3 and the new modified BP-to-height ratio (NMBPHT), 4,5 have been reported to provide better screening performance than the original BP-to-height ratio. However, a recent guideline changed the BP percentiles values in children and adolescents, 6 virtually nullifying these findings.…”
Section: New Modifications Of the Blood Pressure-to-height Ratio For mentioning
confidence: 99%
“…Factors including accuracy, simplicity, cost, and easy use are important for developing a new diagnostic tool for assessing and monitoring BP in pediatrics 4 . As a simplified tool for HBP screening, Modified BPHRs (MBPHR3 and MBPHR7) have been used as alternative methods for HBP screening by considering different heights and BP growth rates in young children 13,16 …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Ma et al 16 reported that a new modified BP to‐height ratio MBPHR3 represented as BP/(height + 3 (13‐age) was superior to MBPHR7 in Chinese children for HBP screening.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of these formulas is the simplicity of data needed to evaluate a child's BP status, including only office BP values and height. Although the initial blood‐pressure‐to‐height ratio was appealing in terms of ease to use, the newer modified blood‐pressure‐to‐height ratios [BP/(height (cm) + 7 (13‐age), and BP/(height + 3 (13‐age)] 7,8 may further compel the physician to familiarize and memorize more complex mathematical formulas. This could be a first limitation for their use in clinical practice beyond epidemiological studies, in which statistical formulas facilitate the calculation of the modified ratios.…”
mentioning
confidence: 99%